2012
DOI: 10.1038/leu.2012.269
|View full text |Cite
|
Sign up to set email alerts
|

MMSET stimulates myeloma cell growth through microRNA-mediated modulation of c-MYC

Abstract: Multiple myeloma (MM) represents the malignant proliferation of terminally differentiated B cells, which, in many cases, is associated with the maintenance of high levels of the oncoprotein c-MYC. Overexpression of the histone methyltransferase MMSET (WHSC1/NSD2), due to t(4;14) chromosomal translocation, promotes the proliferation of MM cells along with global changes in chromatin; nevertheless, the precise mechanisms by which MMSET stimulates neoplasia remain incompletely understood. We found that MMSET enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 53 publications
(76 reference statements)
2
69
0
Order By: Relevance
“…[74][75][76][77] Although MMSET-derived peptides were frequently identified on t(4;14) myeloma samples, we also detected MMSET peptides in the HLA ligandomes of a t(4;14)-negative patient and 1 t(4;14)-negative MCL (U266). Strikingly, functional characterization by ELISPOT revealed memory T-cell responses targeting these MMSET-derived epitopes exclusively in myeloma patients and not in HV.…”
Section: Discussionmentioning
confidence: 90%
“…[74][75][76][77] Although MMSET-derived peptides were frequently identified on t(4;14) myeloma samples, we also detected MMSET peptides in the HLA ligandomes of a t(4;14)-negative patient and 1 t(4;14)-negative MCL (U266). Strikingly, functional characterization by ELISPOT revealed memory T-cell responses targeting these MMSET-derived epitopes exclusively in myeloma patients and not in HV.…”
Section: Discussionmentioning
confidence: 90%
“…But we have not identified the exact adhesion molecule(s) nor cytokine(s)/chemokines(s) mediating the colonization process (data not shown). It is reported that NSD2 can promote myeloma proliferation by modulating c-MYC through microRNA (50). Whether microRNA network is involved in NSD2-mediated myelomagenesis requires further investigation.…”
Section: Challenges Of Targeting Epigenetic Modulators For Therapymentioning
confidence: 99%
“…However, the excess H3K36me2 forces local accumulation of H3K27me3 at a subset of genes, including tumor suppressors. MM cells with t(4;14) translocation are sensitive to EZH2 inhibitors, indicating that the accumulation of EZH2 and H3K27me3 at tumor suppressor loci enhances myeloma cell proliferation [18,65]. Interestingly, in other cancers besides MM, EZH2 and NSD2 are coregulated in an EZH2/NSD2 oncogenic axis [66].…”
mentioning
confidence: 99%